Investigations of upper crossed syndrome’s characteristics in dental students - Srijessadarak, Thanaporn; Sae-Lee, Daraporn; Paungmali, Aatit; mato, lugkana; wanpen, sawitri; Bumrerraj, Sauwanan; Boonprakob, Yodchai (Journal of Associated Medical Sciences, 2017)
Background: From biomechanical dimension, working position of dentist is a prolonged trunk forward bending and forward shoulder posture during clinical practice. It can be assumed that dentists have a high risk of neck or shoulder pain, and upper thoracic pain. These conditions may lead to upper crossed syndrome (UCS) which is consisted of pectoral and neck extensor muscles tightness with scapular and neck flexor muscles weakness. Objectives: To determine craniovertebral angle, pectoralis minor length test, craniocervical flexion test, and scapular muscles strength tests in dental students. Materials and methods: A cross-sectional study was conducted in 220 dental students in 1-6 grades at KhonKaen University. The participants were received physical examination. Length testing of neck extensor muscles was measured by craniovertebral angle, length testing of pectoral muscles was measured by pectoralis minor length test, strength of neck flexor muscles was measured by craniocervical flexion test, and strength of scapular muscles was measured by handheld dynamometer. Results: The result found that the average craniovertebral angle was 50.76±6.99 degrees. The average length of pectoralis minor muscles were 5.44±1.29 and 5.46±2.14 centimeters, on right and left side, respectively. The average strength of neck flexor muscles was 28.55± 2.29 millimeter of mercury (mmHg). The average strength of scapular muscles which consist of 1) serratus anterior muscles were 7.99±2.08 kilogram (kg) on the right side and 7.77±2.19 kg on the left side 2) rhomboid muscles were 10.03±2.83 kg on the right side and 9.86±2.79 kg on the left side 3) middle trapezius muscles were 12.79±2.57 kg on the right side and 12.66±2.55 kg on the left side 4) lower trapezius muscles were 12.43±2.41 kg on the right side and 12.58±2.39 kg on the left side. Conclusion: Dental students trend to have tightness of neck extensor and pectoral muscles, whereas strength of neck flexor and scapular muscle are normal.